Reduced residual gene expression of nuclear factor of activated T cells‐regulated genes correlates with the risk of cytomegalovirus infection after liver transplantation. Issue 3 (26th March 2014) - Steinebrunner, N.; Sandig, C.; Sommerer, C.; Hinz, U.; Giese, T.; Stremmel, W.; Zahn, A.
Abstract Background Pharmacokinetic monitoring of calcineurin inhibitors (CNIs) is unsatisfactory because, at comparable blood concentrations, side effects vary considerably. We recently confirmed the applicability of a pharmacodynamic (PD) assay that measures the suppression of CNI target genes, specifically the suppression of nuclear factor of activated T cells (NFAT)‐regulated genes in liver transplant (LT) recipients. The aim of this prospective study was to prove the clinical reliability of this assay. Therefore, we quantified the residual gene expression (RGE) of NFAT‐regulated genes and evaluated the association between the RGE of NFAT‐regulated genes and the incidence of cytomegalovirus (CMV) infection. Patients and methods In 20 LT recipients, 10 patients on cyclosporine (CsA) and 10 patients on tacrolimus (Tac) therapy, who presented with CMV infection, the RGEs of interleukin‐2, interferon‐γ (IFNγ), and granulocyte–monocyte colony‐stimulating factor were measured and compared with the RGEs of these cytokines in 40 healthy dose‐matched LT controls. Results CsA‐treated CMV patients demonstrated a lower RGE of all NFAT‐regulated genes compared with controls (30 ± 17 vs. 44 ± 20, P = 0.067). For IFNγ, the level of significance was reached (26 ± 17 vs. 43 ± 17, P = 0.0125). Daily CsA dosage, CsA baseline (C0) and 2 h (C2) concentrations were comparable (CsA dosage 169 mg/day vs. 165 mg/day; CsA C0 94 μg/L vs. 85 μg/L; CsA C2 389 μg/L vs. 381 μg/L). In addition, Tac‐treated CMV patients demonstrated a lower RGE of all NFAT‐regulated genes compared with controls (68 ± 25 vs. 84 ± 22, P = 0.0769). Analogous to CsA‐treated CMV patients, the level of significance was reached for IFNγ (61 ± 24 vs. 88 ± 29, P = 0.0154). Daily Tac dosage and Tac 1.5 h concentrations (C1.5) were comparable in both groups (Tac dosage 4 mg/day vs. 4 mg/day; Tac C1.5 8 μg/L vs. 10 μg/L), whereas Tac C0 concentrations were significantly higher in controls (Tac C0 4 μg/L vs. 6 μg/L, P = 0.0276). Conclusion Measuring the RGE of NFAT‐regulated genes is appropriate to assess the risk of infections in LT recipients. Measuring the RGE of IFNγ is particularly suitable to assess the risk of CMV infection. PD monitoring of CNIs in LT recipients is an approach to individualize immunosuppression, which may help to reduce infectious complications.